3-methylcrotonyl Coenzyme A (CoA) carboxylase complex is involved in the Xanthomonas citri subsp. citri lifestyle during citrus infection - Tomassetti, Mauro (2018)
Fil: Fil: Tomassetti, Mauro. Universidad Nacional de Rosario. Facultad de Ciencias Bioquímicas y Farmacéuticas. Instituto de Biología Molecular y Celular de Rosario (IBR-CONICET); Argentina.